The Increase in Paraoxonase 1 Is Associated With Decrease in Left Ventricular Volume in Kidney Transplant Recipients - Philip W. Connelly (Frontiers Media S.A., 2021)
Background: Patients on dialysis have impaired cardiac function, in part due to increased fluid volume and ventricular stress. Restored kidney function through transplantation reduces left ventricular volume in both systole and diastole. We previously reported that the decrease in NT-proB-type natriuretic peptide (NT-proBNP) was associated with a decrease in adiponectin. Paraoxonase 1 (PON1) has been inversely associated with cardiovascular outcomes. We now report the association of changes in PON1 with changes in left ventricular volume and left ventricular mass after kidney transplantation.Design: Patients on dialysis were assessed at baseline and 12 months after kidney transplantation (n = 38). A comparison group of patients on dialysis who were not expected to receive a transplant in the next 24 months were studied (n = 43) to determine if the change of PON1 with kidney transplantation achieved a significance greater than that due to biologic variation. Left ventricular volume and mass were determined by cardiac magnetic resonance imaging. PON1 was measured by arylesterase activity and by mass.Results: PON1 mass and activity were not different between the groups at baseline. Both PON1 mass and activity were increased post-kidney transplantation (p < 0.0001 for change). The change in PON1 mass (p = 0.0062) and PON1 arylesterase activity (p = 0.0254) were inversely correlated with the change in NT-proBNP for patients receiving a kidney transplant. However, only the change in the PON1 mass, and not the change in PON1 arylesterase, was inversely correlated with the change in left ventricular volume (ml/m2.7) (p = 0.0146 and 0.0114 for diastolic and systolic, respectively) and with the change in hemoglobin (p = 0.0042).Conclusion: Both PON1 mass and arylesterase activity are increased by kidney transplantation. The increase in PON1 mass is consistent with a novel relationship to the increase in hemoglobin and decrease in left ventricular volume and NT-proBNP seen when kidney function is restored.